Pengaruh Kualitas Pelayanan dan Kepemimpinan Pemerintah Desa Terhadap Kepuasan Masyarakat: Studi di Desa Didiri Kecamatan Pamona Timur Kabupaten Poso - Lumaya, Novelia Vionita; Guampe, Feliks Arfid; Kawani, Fredrik Bastian; Kayupa, Olvit Olniwati (STAI Darul Kamal NW Kembang Kerang, 2024)
This study aims to analyze the effect of service quality and village government leadership on community satisfaction. This study was conducted in Didiri village, East Pamona District, Poso Regency from July to August 2023. This study used a quantitative approach. The study population was 115 households. The sampling technique used was simple random sampling with a total sample of 92 households. The research data was obtained by distributing questionnaires to 92 respondents. Data analysis using nonparametric inferential statistical techniques. The results showed that the quality of service and leadership partially had a positive and significant effect on community satisfaction. Simultaneously, service quality and leadership also have a significant influence on community satisfaction.